2019
DOI: 10.1002/adts.201900065
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Dynamics Simulation of Nanofilm Boiling on Graphene‐Coated Surface

Abstract: Molecular dynamics (MD) simulations are conducted to investigate the effect of graphene coating on nanofilm boiling on an atomically smooth surface. Transition of boiling modes from normal evaporation to explosive boiling is observed on both bare and graphene-coated surfaces. The onset temperature of explosive boiling on the graphene-coated surface is approximately 170 K, which is extremely close to the value of approximately 160 K on the bare surface. A hydrophobic surface is also artificially fabricated to v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…As a result, only two regimes can be defined: nucleate boiling and film-like (or nanofilm) boiling, an observation consistent with the literature. 23,24,26 This transition to film-like boiling takes place when the energy provided through the solid wall causes rapid vapor-phase expansion, which is not balanced by an adequate supply of liquid in the proximity of the solid−liquid interface.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As a result, only two regimes can be defined: nucleate boiling and film-like (or nanofilm) boiling, an observation consistent with the literature. 23,24,26 This transition to film-like boiling takes place when the energy provided through the solid wall causes rapid vapor-phase expansion, which is not balanced by an adequate supply of liquid in the proximity of the solid−liquid interface.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Molecular dynamics (MD) has been widely employed in the last few years to provide molecular-scale insights into the complexity of boiling phase change at the nano/micro-scale. , Previous attempts at the MD level investigated extensively the role of wettability in heat transfer performances for Lennard–Jones (LJ) liquid argon systems. Tang et al studied the effect of bare and graphene-coated surfaces for atomically smooth solid wall systems and their influence on the critical heat flux (CHF) and transition to film (explosive) boiling for liquid LJ argon. A local, non-uniform heating spot was investigated by Yamamoto and Matsumoto with particular attention to wettability heterogeneities on smooth (flat) solid walls.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…MD simulation models calculate the trajectories of atoms and molecules over time and hence provide the detailed physics of phase transition at interfacial regions between two phases. [44][45][46][47][48][49][50] To gain insights on the atomistic picture of phase transition process, we use MD models that simulate an evaporating thin liquid film on nanostructures, as illustrated in Figure 2a. The detailed view in Figure 2b shows the interactions between liquid and vapor molecules at the interface, representing accommodation and reflection processes.…”
Section: Direct Statistical Measurements Of Accommodation Coefficients From Molecular Dynamics Modelsmentioning
confidence: 99%
“…Qasemian et al [19] studied the explosive boiling of a thin argon nanofilm on conical Al-Cu-based nanostructures and found that the surface with a Cu-Al nanostructure has better heat transfer efficiency than the surface with a single-metal nanostructure. Tang et al [20] investigated the boiling of nanofilm on a single-layer graphene-coated Cu-like surface, and found that the heat transfer of the nanofilm during boiling is barely affected by the single-layer graphene coating. However, Refs.…”
Section: Introductionmentioning
confidence: 99%